The Bradyrhizobium uaiense strain UFLA 03-164T enhanced yield performance of cowpea in soils with low or high phosphorus content - Jóice Xavier de Sousa; Andreza de Jesus Correia; Antonio Jilson Cruz Dias; Caeline Castor da Silva; Patrícia Lopes Leal; Juan Manuel Anda Rocabado; Fatima Maria de Sousa Moreira; Rafaela Simão Abrahão Nóbrega (Bioscience Journal, 2022)
The objective of this study was to evaluate the agronomic efficiency of rhizobia strains already approved or in the selection stage for cowpea, in the Recôncavo da Bahia region, Brazil. Two field experiments were performed in the municipalities of Cruz das Almas and Maragogipe, Bahia, Brazil. A randomized block design was used with seven nitrogen sources and four replicates. Nitrogen sources consisted of the strains UFRB FA51B1, UFRB BA72C2-1, UFLA 03-164T, UFLA 03-84, INPA 03-11B, and two controls without inoculation, one with mineral nitrogen and another without. All the strains nodulated cowpea. The efficiency of the strains was determined by the number of nodules, nodule dry matter, total dry matter, grain yield, nitrogen accumulation in shoots and grain, and relative efficiency. The strain UFLA 03-164T can be recommended for biomass production, green manure, and promotion of grain yields in both soils. In Maragogipe, the UFLA 03-84 and INPA 03-11B strains can be recommended for biomass production, green manure, and promotion of grain yields. The UFLA 03-164T strain showed great potential to promote and grain yield in the two municipalities studied. The strain INPA 03-11B can be recommended for Maragogipe soil. UFLA 03-84 can also be recommended to increase grain yield in Cruz das Almas.